Acyl-CoA:Diacylglycerol Acyltransferase 1 Expression Level in the Hematopoietic Compartment Impacts Inflammation in the Vascular Plaques of Atherosclerotic Mice. - Nemanja Vujic; Jess Porter Abate; Stefanie Schlager; Tovo David; Dagmar Kratky; Suneil K Koliwad (PLoS ONE)
The final step of triacylglycerol synthesis is catalyzed by acyl-CoA:diacylglycerol acyltransferases (DGATs). We have previously shown that ApoE-/-Dgat1-/- mice are protected from developing atherosclerosis in association with reduced foam cell formation. However, the role of DGAT1, specifically in myeloid and other hematopoietic cell types, in determining this protective phenotype is unknown. To address this question, we reconstituted the bone marrow of irradiated Ldlr-/-mice with that from wild-type (WT→ Ldlr-/-) and Dgat1-/-(Dgat1-/-→ Ldlr-/-) donor mice. We noted that DGAT1 in the hematopoietic compartment exerts a sex-specific effect on systemic cholesterol homeostasis. However, both male and female Dgat1-/-→ Ldlr-/-mice had higher circulating neutrophil and lower lymphocyte counts than control mice, suggestive of a classical inflammatory phenotype. Moreover, specifically examining the aortae of these mice revealed that Dgat1-/-→ Ldlr-/-mice have atherosclerotic plaques with increased macrophage content. This increase was coupled to a reduced plaque collagen content, leading to a reduced collagen-to-macrophage ratio. Together, these findings point to a difference in the inflammatory contribution to plaque composition between Dgat1-/-→ Ldlr-/-and control mice. By contrast, DGAT1 deficiency did not affect the transcriptional responses of cultured macrophages to lipoprotein treatment in vitro, suggesting that the alterations seen in the plaques of Dgat1-/-→ Ldlr-/-mice in vivo do not reflect a cell intrinsic effect of DGAT1 in macrophages. We conclude that although DGAT1 in the hematopoietic compartment does not impact the overall lipid content of atherosclerotic plaques, it exerts reciprocal effects on inflammation and fibrosis, two processes that control plaque vulnerability.